Germination and development of M1 seedlings of two Selliera radicans Cav. accessions subjected to gamma radiation - Soto, Fabián; Peñaloza, Patricia; Oyanedel, Eduardo; Schiappacasse, Flavia; Durán, Oscar; Vidal , Alexis (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2021)
Selliera radicans is a creeping plant native to Chile, New Zealand and Australia. It is increasingly used in the ornamental industry, and there is interest in breeding it to create commercial varieties. The aim of this study was to determine the effects of different doses of gamma radiation applied to the seeds on the germination and development of seedlings (M1) and the LD50 of two accessions of Selliera radicans for use in the induction of mutations. Seeds of the Vichuquén and La Serena accessions were exposed to 0, 100, 200, 300, 400, 500, 600 and 700 Gy from a 60Co source. Weekly germination percentages along with seedling numbers and lengths were recorded. Vichuquén seeds were more sensitive to this physical agent. The LD50 was 243.9 Gy for Vichuquén and 445.6 Gy for La Serena. Seedling lengths reached almost 4 mm for Vichuquén and 11.3 mm for La Serena at 12 weeks after sowing. Doses lower than 200 Gy are recommended since higher doses do not allow the development of seedlings to the extended cotyledon stage. Highlights: This is the first radiosensitivity study for the Goodeniaceae family and therefore for the Selliera genus. This study shows the specific effect of gamma radiation at the level of germination and seedling formation according to accession of origin. This study could be used for the genetic improvement of Selliera radicans via the induction of mutations.